Pro-apoptotic and anti-apoptotic proteins as prognostic factors in diffuse large B-cell lymphoma in adults. - Martín-Reyes, Liliana; Grupo de Investigación en Cáncer y Agentes Infecciosos. Instituto Nacional de Cancerología. Bogotá, D.C., (Pontificia Universidad Javeriana, 2010)
Objective. Our purpose was to evaluate the expression of antiapoptotic proteins Bcl-2 and Bcl-xL, and pro-apoptotic proteins Bad and Bax and their association with survival, in patients with DLBCL. Materials and methods. We analyzed biopsies from 28 patients diagnosed with DLBCL. The expression of the apoptotic regulators was assessed by western blot. The association between protein expression and survival was analyzed by the Kaplan-Meier method and the log-rank test. Results. Bcl-2, Bak, Bad and Bcl-xL proteins were expressed in 78.8, 71.4, 64.3 and 50% of the DLBCL cases, respectively. We found no association between the presence of proteins or their expression levels and overall survival. Both Bad and Bcl-xL were associated with higher disease-free survival (33.3% vs. 20.0%, p LR test= 0,003; 42.9% vs. 14.3%, p LR test= 0.03, respectively). High expression levels of Bad and Bcl-xL were associated with a higher disease-free survival (35.7% vs. 21.4%, p LR test= 0.012 y 42.9% vs. 14.3%, p LR test= 0.045, respectively). Conclusion. Given that expression of the Bad protein in tumors was related to a higher disease-free survival, patients with low expression levels of Bad could be candidates in future therapies oriented towards the inhibition of the anti-apoptotic proteins Bcl-xL and Bcl-2 by using molecules that bind specifically to the BH3 domain. Key words: diffuse large B-cell lymphoma, Bcl-2 protein, Bcl-XL protein, Bad protein, Bax protein, survival analysis